Análise das provas do exame da OAB e do ENADE dos Cursos de Direito do ano de 2012 à luz da taxonomia dos objetivos educacionais de Benjamin Bloom - Bezerra Júnior, Antônio Valdenísio (2016)
The approval in the OAB exam is a legal requirement to all law school bachelors that aim to be a lawyer. Since its adoption, it has undergone several critical about its legality, necessity and even effectiveness. Just like in other countries, the OAB, the guardian of the attorney’s profession, uses a measurement test to select only candidates who demonstrate the essential knowledge, skills and abilities to the practice of law. The effective higher education’s evaluation is a task performed by the MEC, through SINAES, in which ENADE is the component used to measure the student’s evaluation. Through Bloom’s educational objectives taxonomy, this research proposes to find the real nature of the OAB exam, in comparison to ENADE’s one, by mapping the educational objectives required in both tests in the years of 2012. Data obtained from the analysis of the instruments shows that the OAB exam worked in the category of knowledge, and the ENADE focused on the next one, the comprehension.